The need for formulation of Shilajit by its isolated active constituents - Ghosal S.; Lal J.; Singh S.K.; Goel R.K.; Jaiswal A.K.; Bhattacharya S.K. (My University, 2025)
Shilajit, a panacea of oriental medicine, collected from different countries, exhibits overtly different levels of bioactivity. The effects of shilajit, collected from India, Nepal, Pakistan and Soviet Russia, and the effects of organic constituents isolated from a potent shilajit sample, were studied in a number of antistress and CNS activity paradigms. Shilajit from Kumaon (India), Dolpa (Nepal), and a combintion (1:1) of the total ethylacetate extracts (TE) and fulvic acids (FAs), from Kumaon shilajit, produced statistically significant effects in forced swimming‐induced immobility in albino mice; restraint stress and aspirin‐induced gastric ulcers in pylorus ligated albino rats; and augmented the learning acquisition and memory retention in old rats. The potential risk of ingesting shilajit, in the native form as a ‘health product’, was appraised in view of its high stable free radical content and possible contamination with mycotoxin‐producing fungi. Hence, there is an imperative need for formulation of shilajit on the basis of its isolated active constituents (TE and FAs). Additionally, the physical and spectral characteristics of active FAs (bioactivity‐directed) were determined and compared with those of less active and inactive samples. These would provide predictability for selection of FAs for formulation of shilajit. Copyright © 1991 John Wiley & Sons, Ltd.